P-601 Is Medroxiprogesterone acetate (MPA) an adequate alternative to GnRH antagonist in oocyte vitrification for non oncological fertility preservation (FP) and preimplantation genetic test (PGT-A) cycles?. (30th June 2022) - Giles, J; Cruz, M; Cobo, A; Vidal, C; Alama, P; Requena, A; Bosch, E
Abstract: Study question: Can we use MPA as a pituitary inhibitor instead of the GnRH antagonist in ovarian stimulation protocols in non-oncological fertility preservation and PGT-A cycles? Summary answer: MPA can act as a substitute of GnRH antagonist for pituitary suppression in FP and PGT-A cycles, since the results are similar between both groups. What is known already: Progestin-primed ovarian stimulation (PPOS) protocols using exogenous progesterone to replace GnRH analogs during the follicular phase of OS have emerged as an efficient alternative to prevent LH from peaking and have been used successfully in different types of patients. Fertility preservation (FP) and preimplantation genetic testing (PGT-A) have become new emerging areas of assisted reproduction. FP gives women the ability to have children using their own gametes after age-related fertility decline, while PGT-A appears to improve reproductive outcomes in advanced maternal age at increased risk of aneuploid embryos. However, few data are available for both indications regarding PPOS cycle outcomes. Study design, size, duration: Multicenter, retrospective, observational, cohort study conducted in eleven IVIRMA centers attached to private universities. We included a total of 4, 961 cycles of non-oncological fertility preservation that were distributed as follows: n = 494 were stimulated under a PPOS protocol while n = 4, 467 received a GnRH antagonist. Regarding PGT-A cycles, we analyzed 12, 461 treatments, of which n = 686 and n = 11, 775 received MPA and GnRH antagonist, respectively. Cycles were performed from January 2017 to December 2021. Participants/materials, setting, methods: Patients were divided according to the protocol used for preventing premature luteinization during follicular phase of OS. In the MPA group, participants received 10 mg daily administered orally, while in the control group, women received an antagonist once the main follicle reached 13 mm. In FP cycles, ovarian response specific parameters were evaluated, such as endocrine profile and mature oocytes; in PGT-A treatments, main variables were number of biopsied and aneuploid embryos and reproductive outcomes. Main results and the role of chance: Regarding FP's baseline characteristics, age was statistically but not clinically significant between the two groups. Length of ovarian stimulation and total dose of hMG administered were similar in both groups, despite the significantly higher total dose of FSH administered in MPA compared to the GnRH antagonist group (p = 0.008) . Number of mature oocytes retrieved (10.2 [95% CI 9.6-10.8] vs 9 [95% CI 8.8-9.2]) was significantly higher in MPA compared to antagonist group; this trend continued regardless of age (≤ 35 or > 35 years). PGT-A cycles followed the same tendency in terms of demographic characteristics. Length of OS was comparable between groups, whilst the total dose of rFSH and hp-HMG administered in the MPA were significantly higher than that in the GnRH antagonist group. Although the number of MII was comparable and despite the lower number of embryos biopsied in the MPA group (4.5±0.2 vs 4.7±0.06, p = 0.031) the number of aneuploid embryos was similar between the two groups (2.3±0.1 vs 2.4±0.04, p = 0.474), as well as implantation (56% vs. 54% p = 0.359) and clinical pregnancy rate (64.1% vs. 62.1, p = 0.316). The miscarriage rate was significantly lower in the group treated with MPA compared to GnRH antagonists (4.7% vs. 8.2%, p = 0.001). Limitations, reasons for caution: The retrospective nature of this study may be a reason for caution and only association, not causation, can be inferred from the results. Despite being the largest sample size ever reported with PPOS in no oncological FP and PGT-A, the number of patients included is still low. Wider implications of the findings: The administration of PPOS yielded similar or even better results than those observed with GnRH antagonists in terms of oocytes retrieved, rate of aneuploid embryos or clinical results. Therefore, PPOS could be recommended for ovarian stimulation in non-oncological FP and PGT-A cycles as it allows for a more patient-friendly approach. Trial registration number: Not applicable